ANALISIS TINGKAT CEMARAN BAKTERI COLIFORM DI SUNGAI BATANG MASUMAI KABUPATEN MERANGIN - Mesi Diana Sari; Rozana Zuhri; Rivo Yulse Viza (Pendidikan Biologi STKIP YPM Bangko, 2020)
This research is done bucause of the incidence of diarrhea at Batang Masumai District last two years on 2017. There were 159 males and 152 female got diarrhea sufferers. Whereas, on 2018 264 people got diarrheae a and the total was high. In that year, there were 179 children got diarrhea. The purpose of this study was to determine and describe the level of contamination of Coliform bacteria at the Batang Masumai river. The type of the research was experimental research with a quantitative approach. This research was carried out in a biological laboratory with 3 stages. The first stage is water sampling at four parts. The second stage is microbiological analysis (estimator test, assertion test, complementary test). In the estimator test, the Lactose Broth (LB) media is put into a test tube that has been filled with durham tubes as much as 3 tubes, incubated 2x24 hours, and marked with the formation of gas bubbles . In the assertion test, the Briliant Green Lactose Broth (BGLB) media was put into a test tube that had been filled with durham tubes, 1-2 ose suspensions from (positive test) positive were inoculated into a tube containing the media, incubated 2x24 hours and marked with the formation gas. The number of Coliform bacteria in the affirmation test was calculated based on the MPN method. Furthermore, one positive media in the (affirmation test) was inoculated as much as 1 ose into the EosineMetilene Blue (EMB) media so that in the petri dish, it was incubated 2x24 hours, if the colony grew with green metallic characteristics followed by gram staining. Physically tested water samples to analyze temperature. Chemical water sample testing to analyze pH. The third stage is the data analysis stage. Total Coliform bacteria obtained in PulauBaru Village was 1898 cells / 100ml, in Rantau Alai Village was 1898 cells / 100ml, in Salam Buku Village was 1898 cells / 100ml, and in Sungai Mas Village (Ujung Tanjung) was 1898 cells / 100ml.